HISTOLOGY TEST OF TILAPIA (Oreochromis niloticus) ON ADSORBENT PERFORMANCE RESULTS IN LIQUID TREATMENT OF INDUSTRY PULP AND PAPER WASTE - Susila Arita Rachman; Devi Kristianti; Yuanita Windusari (BIOVALENTIA: Biological Research Journal, 2022)
Pulp and paper industry fly ash is categorized as B3 waste, namely hazardous and toxic waste. Liquid waste produced by the pulp and paper industry contains pollutants that are toxic and can cause pathological and histopathological changes in important tissues such as the gills of fish that live in the waters around the disposal. The purpose of this study was to analyze the histology of tilapia on the performance results of fly ash adsorbents in the management of liquid waste in the pulp and paper industry. The research method has 6 treatments, namely the ratio of fly ash to pulp and paper liquid waste (20 g; 1 L) namely P0: 100 % well water control, P1: lowest liquid waste 5 % + 9.5 % well water, P2: 5 % liquid waste fly ash adsorbent + 95 % well water, P3: 6.25 % liquid waste fly ash adsorbent + 93.75 % well water, P4: 7.5 % liquid waste fly ash adsorbent + 92.5 L of well water, P5: 8.75 % fly ash adsorbent + 91.25 % well water, P6: 10 % fly ash adsorbent + 9 % well water. Water quality measurements such as temperature, NH3, pH and DO were carried out. Observation of gill histology used microtechnical method which includes deparaffinization and histological staining (HE). Analysis was carried out on changes in cell morphology in gill tissue. The results showed that the morphology of gill cells in liquid waste pulp and paper 5 % found gill damage in the form of congestion, secondary lamella fusion, secondary filament rupture and goblet proliferation occurred in the treatment of wastewater treatment while Fly ash adsorbent 5 % damaged gills in the form of congestion and fusion of secondary lamellae. From the results of the Fly ash functions can reduce damage to body organs in fish, especially on the gills so that it can reduce the number of deaths in fish compared to treatment without the use of fly ash.